2012
DOI: 10.1590/s1983-51752012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de queimadura de segundo grau superficial em face e pescoço com heparina tópica: estudo comparativo, prospectivo e randomizado

Abstract: Rev Bras Cir Plást. 2012;27(3):383-6 383Treatment of superficial second degree burn of face and neck with topical heparin Treatment of superficial second degree burn of face and neck with topical heparin: a comparative, prospective and randomized study Tratamento de queimadura de segundo grau superficial em face e pescoço com heparina tópica: estudo comparativo, prospectivo e randomizado ABSTRACT Background: New treatment options for thermal injuries are very desirable, especially if they reduce healing time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…In another study, conducted with 20 patients, researchers reported that in those who used collagenase (10 patients), the healing time was shorter than in those who used topical heparin (ten patients) 26 ; sodium heparin, which is known for its anticoagulant action 38 . Researchers have pointed out that the effect of parenteral sodium heparin has been studied on thermal injuries in animals and in humans, with favorable effects 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, conducted with 20 patients, researchers reported that in those who used collagenase (10 patients), the healing time was shorter than in those who used topical heparin (ten patients) 26 ; sodium heparin, which is known for its anticoagulant action 38 . Researchers have pointed out that the effect of parenteral sodium heparin has been studied on thermal injuries in animals and in humans, with favorable effects 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Controversially, Teles et al, 2012 4 reported that that Heparin can be applied safely in the treatment of second degree burns of face and neck, however its beneficial effects need to be proven. Although he said that the heparin group used less non-opioids analgesics than the collagenase group.…”
Section: Discussionmentioning
confidence: 99%
“…Saliba et al [23] studied and popularized the use of heparin in the management of burn wounds with interesting results, and Teles et al [24] performed a comparative prospective, randomized study of heparin and collagenase. The results demonstrated heparin alone was not effective in decreasing healing time or reducing the use of opioids, and did not reduce infection rate significantly between the groups.…”
Section: Facial Burn Wound Managementmentioning
confidence: 99%